Who’s Afraid of Education? - Artem Ingmar Benediktsson (Nordic Journal of Comparative and International Education)
Who’s Afraid of Education? is an ethnodrama in four acts based on data collected at two university colleges in Denmark. The main characters, Myriam and Mahmood, embody the collective voices of seven student teachers, all of whom were in the final year of their teacher education program at the time of the study. The ethnodrama centers on the characters’ experiences, deliberately prioritizing their perspectives over the researcher’s interpretations. The reader is invited to form their own interpretations and to critically reflect on the tension between the characters’ cultural identities and the expectations of a predominantly monocultural educational system. By encouraging a deeper level of engagement with the research findings, the ethnodrama breaks away from conventional academic writing formats, making the research more accessible to a wider audience.